Isolation and quantification of microorganisms from some common milk products within Dhaka city, Bangladesh (Stamford Journal of Microbiology, 2016)
While milk is well known to be a balanced diet with its high nutritional values, conversely milk and milk products may serve as potential substrate for the growth and proliferation of a range of microorganisms which in turn fatally influences mass public health. Current study attempted to examine the likelihood of microbial contamination within some common milk products consumed by the locality of the city of Dhaka, Bangladesh. All samples exhibited the presence of bacterial and fungal contamination within a range of 102-104 cfu/mL and 102-103 cfu/mL, respectively. Among specific pathogens, Staphylococcus spp. was noticed to be the predominant ones and was recovered from 9 samples out of 20 samples in a range of 102-103 cfu/mL. Klebsiella spp. and Vibrio spp. were found within 6 and 9 samples, respectively. Products were also found to be contaminated with Vibrio spp. Study of antibiotic susceptibility test revealed that all the pathogenic bacteria were resistant against most of the commonly used antibiotics of which several isolates showed multi-drug resistant (MDR) trait. Therefore, the presence of pathogenic bacteria with the drug-resistance property in tested milk and milk products overall imparted the necessity of maintaining standardized hygienic handling and processing means for better management of public health.Stamford Journal of Microbiology, Vol.5(1) 2015: 13-17